Taboo Word “Jancuk” Analysis On Youtube Video “Kata Jancuk Berasal dari … - Jawa Jawa Jawa eps. 8” By Comedy Sunday - Ahmad Taufiqurrahman; I Made Astu Mahayana; Sabinus Charles U.H. Lujuwara (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This sociolinguistic study examines the taboo word “jancuk” (also spelled “jancok” or “dancok”) as represented in the YouTube video KATA JANCUK BERASAL DARI … - JAWA JAWA JAWA EPS. 8, a segment from a series dedicated to exploring Javanese language and culture. Drawing on Wardhaugh’s (2006) classification of taboo expression epithets, profanity, vulgarity, and obscenity, and Battistella’s (2005) analysis of linguistic form in relation to societal norms and power structures, the research classifies “jancuk” primarily as obscenity and vulgarity due to its etymological roots in sexual connotations (derived from “di-encuk,” meaning intercourse in Javanese). Despite its inherently taboo nature, the word shows pragmatic versatility in East Javanese contexts, particularly among the “Arek” community in Surabaya, where it functions as a language for expressing frustration or anger, a marker of regional identity, and even a term of solidarity in informal, in-group interactions. The video’s educational approach highlights sociolinguistic dynamics, including code-switching between the rude (ngoko kasar) and polite dialects, regional variation across Java, and the word’s shift from purely negative to multifunctional in simultaneous use. Findings show that the role of taboo words in supporting cultural identity amid globalization and digital propaganda, while also addressing misuse and politeness violations across diverse social contexts. This analysis contributes to broader understandings of taboo language in multilingual Bahasa Indonesia, offering insight for language education, media representation, and intercultural communication